Tools for Environmental Impact Assessment (EIA) Using Diversity Indices - Khan, S. J. (Faculty of Science, University of Jaffna, 2015)
This article gives information regarding the various biodiversity indices which could be used successfully as the tools for undertaking environmental impact assessment.
Keywords: diversity; ecosystem; community